Analysis of Audience Reception on Youtube towar d Gender Construction in the Music Video If I Were a Boy by Beyonce Knowles - Avriyanty, Ria (UI Scholars Hub, 2011)
Youtube is one of the favorite sites to share videos. Moreover,it facilitates the users to give a free and direct comment toward the videos they watch. The research examines the music video entitled If I Were a Boy (2010) by Beyonce Knowles as well as the authentic responses from the viewers in Youtube. I argue that this music video creates a conventional gender construction which perpetuates the patriarchal norms in the society. As an attempt to give a new perspective on the similar kind of research, I do not stop at this point. Applying the concept of encoding-decoding by Stuart Hall (1973), I found the audience’s being critical which can be seen from the total number of the responses and the controversy within. In accordance to the three hypothetical position argued by Hall, I found a different portion of the audience in each position. As a matter of fact, this phenomenon contributes to the cyber culture in which Youtube is seen as a functional space to make meaning of a digital text and negotiate with the constructed stereotype by giving responses.